1989
DOI: 10.1037/0022-3514.57.6.1024
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional optimism and recovery from coronary artery bypass surgery: The beneficial effects on physical and psychological well-being.

Abstract: The effect of dispositional optimism on recovery from coronary artery bypass surgery was examined in a group of 51 middle-aged men. Patients provided information at three points in time--(a) on the day before surgery, (b) 6-8 days postoperatively, and (c) 6 months postoperatively. Information was obtained relating to the patient's rate of physical recovery, mood, and postsurgical quality of life. Information was also gathered regarding the manner in which the patients attempted to cope with the stress of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
538
6
21

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 799 publications
(605 citation statements)
references
References 50 publications
33
538
6
21
Order By: Relevance
“…Observamos que grande parte das publicações não utiliza a denominação "felicidade", mas o termo "bemestar subjetivo" (Scheier et al, 1989;Khoo e Bishop, 1997;Ryan e Deci, 2000;Scheier et al, 2001;Diener e Biswas-Diener, 2002;Cloninger, 2004). Isto deriva da dificuldade em abordar-se diretamente a felicidade, de modo que muitos pesquisadores preferem mensurar o bem-estar subjetivo relatado pelas pessoas felizes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Observamos que grande parte das publicações não utiliza a denominação "felicidade", mas o termo "bemestar subjetivo" (Scheier et al, 1989;Khoo e Bishop, 1997;Ryan e Deci, 2000;Scheier et al, 2001;Diener e Biswas-Diener, 2002;Cloninger, 2004). Isto deriva da dificuldade em abordar-se diretamente a felicidade, de modo que muitos pesquisadores preferem mensurar o bem-estar subjetivo relatado pelas pessoas felizes.…”
Section: Discussionunclassified
“…Existem pesquisas que demonstram uma relação do otimismo com: (1) aumento no bem-estar subjetivo (Scheier et al, 1989;Khoo e Bishop, 1997); (2) elevação da auto-estima (Dunn, 1996); (3) baixo índice de depressão (Carver e Gaines, 1987;Marshall e Lang, 1990); (4) baixo índice de emoções negativas (Curbow et al, 1993;King et al, 1998); (5) alto índice de satisfação com a vida (Chang, 1998); (6) boa saúde (Scheier et al, 1999); (7) menor taxa de mortalidade associada a câncer (Schulz et al, 1996); e (8) melhor qualidade de vida (Wrosch e Scheier, 2003).…”
Section: Otimismo E Resiliênciaunclassified
“…Research in positive psychology has identified a host of benefits of optimistic, positive thinking in social relationships, health, and happiness (Carver, Kus, & Scheier, 1994;Peterson, 2000;Scheier et al, 1989;Seligman & Csikszentmihalyi, 2000;Seligman & Schulman, 1986). …”
Section: Why Would People Prescribe Optimism?mentioning
confidence: 99%
“…Existing literature has indicated that individual differences in characteristics such as optimism and pessimism contribute to variability in levels of emotional distress in stressful situations (e.g., Chang, 2001;Scheier & Carver, 1985, 1992. For example, Scheier, Matthews, and Owens (1989) found that patients' levels of optimism inversely predicted their levels of distress before surgery, above and beyond the effects of relevant medical variables.…”
Section: Introductionmentioning
confidence: 99%